Tafsir Tarbawi Sebagai Paradigma Qur'ani dalam Reformulasi Pendidikan Islam - Ali Mudlofir (IAIN Ponorogo, 2011)
As a complete way of life for of Muslims, the Qur’an gives guidelines about education, in addition to the theology and the law. The history of thought of Muslims presented several paradigms of interpretation of the Qur’an, rangefrom the strictfundamentalist to the liberal. Thisfact indicates that the demands of Muslims to the sciences of the Qur’an and the results of them always arouse throughout the history. Even the enthusiasts ofstudy the Qur’an in the contemporary era insist that the Qur’an gives the widespread possibilities of meanings and themes. Taking into account the contemporary demands to education, it does not matter with using any paradigm of interpretation, but the choice to use a thematic method (al-tafsir al‑mawdu ‘i) is the most appropriate choice. Thematic method will generate a thorough understanding of the concept of Islamic education, and this is the right way to establish the discipline of Qur ’anic educational exegesis (al-tafsir al-tarbawi). In essence, thinkers on Islamic education should continuously develop elaboration of the concept ofIslam which views human beings have the their potential to achieve the perfection by integrating the innate factors and the environmental ones.